THE EFFECTIVENESS OF AI-BASED CHATBOTS IN ENHANCING ENGLISH AS A FOREIGN LANGUAGE (EFL) LEARNING - Rasmita; Dian Anggraini; Anita Wijayanti; Wienda Gusta; Ryan Hidayat Rafiola (JEE (Journal of English Education), 2026)
The integration of Artificial Intelligence (AI) in education has created new opportunities for English as a Foreign Language (EFL) learning; however, research on the effectiveness of AI-based chatbots in improving students’ language skills and learning motivation remains limited, particularly in EFL contexts. This study investigates the impact of AI-based chatbots on students’ speaking and writing skills, as well as their motivation toward learning English. A quasi-experimental design was employed involving two groups of students: an experimental group using AI-based chatbots and a control group receiving traditional instruction. Data were collected through pre-tests, post-tests, questionnaires, and interviews to evaluate students’ achievement and perceptions. The findings revealed that the experimental group showed significantly greater improvement than the control group, with average post-test scores increasing by approximately 18% in speaking and 15% in writing. In addition, students reported higher levels of motivation, confidence, and classroom engagement due to the interactive and immediate feedback provided by the chatbots. These findings suggest that AI-based chatbots can effectively support EFL learning and complement conventional teaching methods by creating more interactive and student-centered learning environments. Future research is recommended to examine the long-term effects of chatbot-assisted learning and explore the integration of more advanced AI features in language education.